The phantom tollbooth - Juster, Norton; Feiffer, Jules Sendak, Maurice (Alfred A. Knopf New York, 2015)
Milo, a young boy with little interest in anything, takes a trip through the Phantom Tollbooth to the Lands Beyond where he meets an enchanting cast of characters that teaches him the importance of words, numbers, ideas, creativity, and enthusiasm for life. Includes an introduction by Maurice Sendak and "Celebrations of The Phantom Tollbooth" by various authors